2002
DOI: 10.5194/angeo-20-1203-2002
|View full text |Cite
|
Sign up to set email alerts
|

Statistical characteristics of low-latitude ionospheric field-aligned irregularities obtained with the Piura VHF radar

Abstract: Abstract. We present a summary of the statistical characteristics of echoes from ionospheric (E-and F-region) fieldaligned irregularities obtained with the Piura VHF radar. This radar is located at ∼7.0 • dip latitude, just outside the equatorial electrojet (EEJ) region. Our results are based on (1) intermittent observations made between 1991 and 1999 just few days a year, and (2) continuous observations made between January 2000 and June 2001. During most of the intermittent observations, simultaneous measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
74
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(86 citation statements)
references
References 33 publications
8
74
4
Order By: Relevance
“…Observations on E region FAIs from Kototabang, however, have been limited so far. Echo occurrence and spectral characteristics revealed from these observations have been found to be close to those observed in mid-latitudes and distinctly different from those of equatorial electrojet (for details, see Chau et al, 2002;Patra et al, 2004). It may be noted that these radars are located in the 6-11 • magnetic latitude belt.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Observations on E region FAIs from Kototabang, however, have been limited so far. Echo occurrence and spectral characteristics revealed from these observations have been found to be close to those observed in mid-latitudes and distinctly different from those of equatorial electrojet (for details, see Chau et al, 2002;Patra et al, 2004). It may be noted that these radars are located in the 6-11 • magnetic latitude belt.…”
Section: Introductionmentioning
confidence: 81%
“…It may be noted that these radars are located in the 6-11 • magnetic latitude belt. Chau et al (2002) have made a detailed investigation on the diurnal and seasonal variations of low-latitude E region FAIs based on Piura radar observations. Patra et al (2004) made a detailed study on the diurnal variation of echo occurrence and spectral parameters based on Gadanki observations and compared it in detail with those reported by Chau et al (2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As suggested by Tsunoda and Ecklund (2004) the lack of seasonal variability over Jicamarca might be due to weaker sporadic E s activities observed in Jicamarca's longitude sector. However, Chau et al (2002) have shown that VHF radar echoes associated with E s layers in the Jicamarca sector -observed with the Piura radar (∼900 km north of Jicamarca) -are stronger and more frequent during the southern summer, i.e. December solstice.…”
Section: Discussionmentioning
confidence: 99%
“…There is still an open question on the reverse effect: how do the E-region irregularities at the foot of the flux tubes observed at the equator affect the formation of Spread F irregularities there? A correlation study was performed using the Piura VHF radar and Jicamarca simultaneously (Chau et al, 2002). Piura observed E-and F-region irregularities and Jicamarca the latter.…”
Section: Satellites Rockets and Other Radars And Radar Techniquesmentioning
confidence: 99%